REVISION OF PEDICULARIS SERIES TENUIROSTRES (OROBANCHACEAE) - Mill, R. R. (Edinburgh Journal of Botany, 2011)
Pedicularis ser. Tenuirostres Maxim. (Orobanchaceae) is demonstrated to be the correct name for the group usually referred to as P. ser. Pectinatae Prain. The series is here revised and 12 species are accepted. Its species are centred in the NW Himalaya, particularly Pakistan where there is much local infraspecific variation. Two species are excluded from the series: Pedicularis rhynchotricha P.C.Tsoong from China (Xizang) is placed in P. ser. Rhynchotrichae R.R.Mill and P. birmanica Bonati is confirmed as a member of P. ser. Brevifoliae (Prain) Bonati. One new species of Pedicularis ser. Tenuirostres is described: P. yamazakiana R.R.Mill from Nepal, which was formerly confused with P. pectinata subsp. palans Prain. Pedicularis jainii Aswal & Mehrotra is demonstrated to be a superfluous name for P. pyramidata Royle ex Benth. Pedicularis kashmiriana var. ornata Pennell is considered to be indistinguishable from P. pyramidata although P. kashmiriana var. kashmiriana is a recognisable taxon. An IUCN conservation assessment is proposed for Pedicularis rhynchotricha and for each taxon within P. ser. Tenuirostres.